Pengaruh Iradiasi Sinar Gamma terhadap Pertumbuhan Stek Tunas Apikal dan Aksilar Kopi Arabika - Meynarti Sari Dewi Ibrahim; Enny Randriani (Jurnal Tanaman Industri dan Penyegar, 2020)
The Arabica coffee is predominantly self-pollinated plants thereby contributing to low genetic diversity. The effort to increase the genetic diversity of Arabica coffee through crossing strategy is time-consuming, and induce mutation is necessary to enhance the rate of genetic variation. The aims of this study were to observe the effect of gamma-ray irradiation on the growth of apical and axillary bud cuttings and to determine the value of LD50 on apical cuttings and Arabica coffee axillaries. The study was conducted at the Tissue Culture Laboratory, Industrial and Beverage Crops Research Institute, from January to December in 2018.. The planting material that was irradiated was Arabica coffee plantlets resulting from somatic embryogenesis propagation. Irradiation is carried out at the National Nuclear Energy Agency. The irradiated plantlets were cut and subcultured onto MS medium without growth regulators, 30 g L-1 sucrose, and 2.5 g L-1 phytagel were added. The design used a completely randomized design with 10 replications. The treatments tested were the dose of gamma-ray irradiation (0, 10, 20, 30, 40, and 50 Gy). The results showed that gamma-ray irradiation had an effect on all observed parameters. The mortality percentage of apical shoot cuttings began to be found at 30 Gy, while axillary cuttings at 20 Gy increased with an increasing dose of gamma-ray irradiation. The number of shoots and leaves varied between irradiation doses on both apical and axillary cuttings. The LD50 value of apical shoot cuttings was 36.80 Gy, while axillary cuttings were 22.24 Gy